Graphic organizer instruction in teaching reading comprehension to low-proficient English as a Second Language (ESL) Students / Umaiyal A/P Krishnan and Hui Min Low - Krishnan, Umaiyal; Hui, Min Low (Universiti Teknologi MARA, Kedah, 2019)
This study aimed to investigate the effects of graphic organizer (GO) instruction to teach reading comprehension to low-proficient ESL Form 2 students in Malaysia. The study utilized a quasiexperimental design to examine reading comprehension performance of two groups of students, with and without the provision of GO instruction. There were 15 students in each group who were administered with a pre-test and a post-test. The results from this study supported the positive effects of GO instruction in improving reading comprehension performance. Students who had received GO instruction were found to be more able to identify the keywords in the passages and answer the questions using own words. Besides that, they also performed better in answering average- to high-level reading comprehension questions. The findings offer new empirical evidence to support the schema theory in explaining the processes in reading comprehension. Given the visual representations in the GO instruction, the textual information from the reading passages can be more readily mapped with the students' existing mental schemas. This process was found to be useful to aid low-proficient ESL students in performing reading comprehension tasks.